Water Stress, Peri-Urbanization, and Community-Based Water Systems: A Reflective Commentary on the Metropolitan Area of Mexico City - Chen, Yu; Bilton, Amy M. (Frontiers in Sustainable Cities, 2022)
With a population of over 22 million, Mexico City’s metropolitan area is facing enormous water security challenges. Its supply heavily relies on overdraft of groundwater and import from neighboring basins, leading to problems such as subsidence and raising concern over its sustainability. The impacts of the water stress in Mexico City are highly unequal across the metropolitan area and more severe in low-income neighborhoods in the peri-urban areas. This paper will first review the current water stress in Mexico City, its impacts on vulnerable communities, as well as some existing technical and institutional approaches aiming to tackle these challenges. I will then focus on the community-based water management systems in Mexico City’s peri-urban areas, based on the case of Tecámac, one of the 59 municipalities that form the conurbation area. I will discuss the local water politics in the municipality, the historical evolution of the community-based water system, as well as its current agenda. This essay highlights the importance to incorporate the community-based water systems in the development of a solution to the water crisis in megacities like Mexico City: not only do they serve as provider of potable water to a considerable number of households, but they also represent a resistance to the speculation-driven (peri) urbanization and an agent for promoting comprehensive water reform in the country.